Object-Oriented Discussions in Philosophy and Literature: A New Narratology? (KULT_online, 2025)
In their book, Marie-Laure Ryan and Tang Weisheng aim to lay the foundation for a new narratological approach for the use and representation of objects in narrative, exploring object as a basic category of narrative and the theoretical function of objects in narrative. To do so, they draw on the premises of what they summarize as “new object philosophy” that focuses on the agency of objects. The central goal of the book is to reconceptualize the object as a core concept of narrative theory and to lay the foundation for a broad new field of research.